Complete Genome Sequences of Three Clinical Listeria monocytogenes Sequence Type 8 Strains from Recent German Listeriosis Outbreaks - Fischer, Martin A. (Microbiol Resour Announc, 2021)
We report here the closed genome sequences of three clinical Listeria monocytogenes strains of multilocus sequence typing (MLST) sequence type 8 (ST8). These strains are representatives of three separate listeriosis outbreak clusters (Alpha1, Pi4, and Sigma1) that affected Germany between 2012 and 2020.